In vitro growth response of Phytophthora cactorum, P. nicotianae and P. × pelgrandis to antibiotics and fungicides - Pánek, M; Tomšovský, M (Folia microbiologica, 2017)
The reactions of isolates of Phytophthora cactorum, P. nicotianae and P. × pelgrandis to metalaxyl, mancozeb, dimethomorph, streptomycin and chloramphenicol were tested to obtain information about the variability of resistance in these pathogens. Distinct genetic groups showed significant differences in resistance to all tested substances except streptomycin. In response to streptomycin, the growth inhibition rates of distinct groups did not differ significantly. The most remarkable differences were detected in the reactions to chloramphenicol and metalaxyl. Discriminant analysis evaluating the effect of all substances confirmed the differences among the groups, which are in agreement with the differences revealed by earlier DNA analyses.
Keywords: Fungicides, Industrial; Oomycetes; Population; Nicotiana; nemoci rostlin; Discriminant analysis; průmyslové fungicidy; antibakteriální látky; Anti-Bacterial Agents; tabák; Chemical control; Plant Diseases; Phytophthora